First record of Vespa crabro Linnaeus (Hymenoptera: Vespidae) in western North America with a review of recorded species of Vespa Linnaeus in Canada - Bass, Amber; Needham, Karen; Bennett, Andrew M.r. (Zootaxa, 2022)
Vespa crabro Linnaeus is newly reported as an adventive species in British Columbia, Canada which is the first record of this invasive species in western North America. The specimen of V. crabro was identified using morphological diagnostic keys and by comparison to authoritatively identified specimens. DNA barcoding provided support that the British Columbia specimen is conspecific with sequenced specimens of V. crabro. It is not possible to be certain of the origin of the specimen, but the DNA barcode was identical to sequence from specimens of V. crabro from South Korea. DNA barcoding was also performed on morphologically identified specimens of Vespa simillima and Vespa soror collected previously in British Columbia and the sequences were closest to V. simillima and V. soror Genbank sequences, respectively. There is no evidence that any of these species have established populations in the province. We provide diagnostic morphological characters to distinguish Canadian Vespa species from each other including Vespa mandarinia which has recently established populations in British Columbia and Washington State, USA. The potential detrimental impacts of each species are discussed.